PENGARUH LEVERAGE, LIKUIDITAS, UKURAN PERUSAHAAN DAN VOLUME PERDAGANGAN SAHAM TERHADAP RETURN SAHAM PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2020-2022 - Choirudin, Moch Amin; Istanti, Sri Layla Wahyu (Universitas YPPI Rembang, 2024)
The aim of this research is to determine the effect of leverage, liquidity, company size and stock trading volume on stock returns in food and beverage companies listed on the Indonesia Stock Exchange from 2020-2022. This research uses the dependent variable stock returns, while the independent variables are leverage, liquidity, company size and stock trading volume. The population used is 61 food and beverage companies listed on the Indonesia Stock Exchange from 2020-2022, which can be accessed at www.idx.co.id. The documentation method was used to collect data in this research. The purposive sampling method was used to select samples. The research sample consisted of 20 companies and a total of 60 observations. Multiple linear analysis is the data analysis method used. Before the regression is carried out, the classic assumption test is used to obtain the Best Linear Unbias Estimate (BLUE) data. The results of hypothesis testing show that company size has a positive impact on stock return, conversely, leverage, liquidity, and stock trading volume have an insignificant negative impact on stock returns. Keywords: leverage, liquidity, company size, stock trading volume, stock returns